PENGARUH PROFITABILITAS, LEVERAGE DAN ARUS KAS TERHADAP RETURN SAHAM PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Syafira Arifa, - (2019)
This study aims to determine the effect of Profitability proxied with Return on Assets (ROA), Leverage proxied by Debt to Equity Ratio (DER), and Cash Flow proxied by Logarithm Natural Asset toward Stock Returns. Population in this study are consumer goods industry sector companies listed in Indonesia Stock Exchange (IDX) 2015-2017. The technique of determination of the sample using the method of purposive sampling and obtained 12 consumer goods industry sector companies from 41 population, with a research period of three years to obtain 36 units of samples. Data analysis was done using Microsoft Excel 2013 and hypothesis testing in this research using Data Panel Regression Analysis with EViews 9.0 program and significance level of 5%. The result of the research shows that (1) profitability (ROA) has a significant effect positive on stock return, (2) debt policy (DER) has significant effect negative on stock return, (3) cash flow has no significant effect negative on stock return.